2006
DOI: 10.1159/000098873
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Orotate Phosphoribosyl-Transferase Gene Enhances the Effect of 5-Fluorouracil on Gastric Cancer Cell Lines

Abstract: Objective: Orotate phosphoribosyl-transferase (OPRT) is the initial enzyme of the 5-fluorouracil (5-FU) metabolic pathway, converting 5-FU into 5-fluorouridinemonophosphate, which is the most important mechanism of 5-FU activation. We therefore investigated whether overexpression of the OPRT gene enhances sensitivity to 5-FU. Methods: An expression vector of the OPRT gene (pTARGET-OPRT) was transfected into two gastric cancer cell lines, TMK-1 and MKN-45, with low baseline expression levels of OPRT. The sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Inaba et al reported a significantly low activity of OPRT in the 5-FU-resistant cell line by measuring the enzyme activities in the human cancer cell lines, [11]. Taomoto et al also indicated that OPRT overexpression plays an important role in the increased sensitivity of gastric carcinomas to 5-FU chemotherapy [4]. The present result is compatible with those of the earlier studies.…”
Section: Discussionsupporting
confidence: 90%
“…Inaba et al reported a significantly low activity of OPRT in the 5-FU-resistant cell line by measuring the enzyme activities in the human cancer cell lines, [11]. Taomoto et al also indicated that OPRT overexpression plays an important role in the increased sensitivity of gastric carcinomas to 5-FU chemotherapy [4]. The present result is compatible with those of the earlier studies.…”
Section: Discussionsupporting
confidence: 90%
“…tumors were placed in 3-time volumes of ice-cold 10 mM tris-Hcl buffer (pH 7.4), containing 1 mM eDtA and 0.5 mM Dtt and homogenized. oprt activity was determined using a previously described 5-FU phosphorylation assay (14). the supernatant of tumor tissue homogenates was incubated with 20 µM [6-14 c] 5-FU; 50 mM tris-Hcl, pH 8.0; 5 mM Mgcl 2 ; 10 mM naF; 0.5 mM DTT and 4 mM phosphoribosylpyrophosphate at 37˚C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Low intratumor 5-FU levels and its high degradation depend on dihydropyrimidine dehydrogenase (DPYD) activity, an enzyme responsible of drug catabolism [36]. On the other hand, it is important to highlight the key role of an anabolic enzyme, the orotate phosphoribosyltransferase (OPRT), which metabolizes 5-FU to 5-fluorouridine monophosphate in the presence of 5-phosphoribosyl-1-pyrophosphate [37]. In the patent WO2011/052554 [38], inventors claim the discovery of a series of compounds with a DPYD and OPRT inhibitory activity, achieving a decrease in 5-FU gastrointestinal damage and powerful antitumor effects ( Figure 1B).…”
Section: -Fu Derivativesmentioning
confidence: 99%